Characterization of Recombinant B. abortus Strain RB51SOD Toward Understanding the Uncorrelated Innate and Adaptive Immune Responses Induced by RB51SOD Compared to Its Parent Vaccine Strain RB51 - Zhu, Jianguo; Larson, Charles B.; Ramaker, Megan A.; Quandt, Kimberly; Wendte, Jered; Ku, Kimberly; Chen, Fang; Jourdian, George; Vemulapalli, Ramesh; Schurig, Gerhardt G.; He, Yongqun "Oliver" (Frontiers in Cellular and Infection Microbiology, 2011)
Brucella abortus is a Gram-negative, facultative intracellular pathogen for several mammals, including humans. Live attenuated B. abortus strain RB51 is currently the official vaccine used against bovine brucellosis in the United States and several other countries. Overexpression of protective B. abortus antigen Cu/Zn superoxide dismutase (SOD) in a recombinant strain of RB51 (strain RB51SOD) significantly increases its vaccine efficacy against virulent B. abortus challenge in a mouse model. An attempt has been made to better understand the mechanism of the enhanced protective immunity of RB51SOD compared to its parent strain RB51. We previously reported that RB51SOD stimulated enhanced Th1 immune response. In this study, we further found that T effector cells derived from RB51SOD-immunized mice exhibited significantly higher cytotoxic T lymphocyte (CTL) activity than T effector cells derived from RB51-immunized mice against virulent B. abortus-infected target cells. Meanwhile, the macrophage responses to these two strains were also studied. Compared to RB51, RB51SOD cells had a lower survival rate in macrophages and induced lower levels of macrophage apoptosis and necrosis. The decreased survival of RB51SOD cells correlates with the higher sensitivity of RB51SOD, compared to RB51, to the bactericidal action of either Polymyxin B or sodium dodecyl sulfate (SDS). Furthermore, a physical damage to the outer membrane of RB51SOD was observed by electron microscopy. Possibly due to the physical damage, overexpressed Cu/Zn SOD in RB51SOD was found to be released into the bacterial cell culture medium. Therefore, the stronger adaptive immunity induced by RB51SOD did not correlate with the low level of innate immunity induced by RB51SOD compared to RB51. This unique and apparently contradictory profile is likely associated with the differences in outer membrane integrity and Cu/Zn SOD release.